Election of Bishop Bazyli (Doroszkiewicz) as the Metropolitan of the Polish Autocephalous Orthodox Church as part of the religious policy of the Polish state - Dudra, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The election of superiors in the Polish Autocephalous Orthodox Church was one of the key elements in the religious policy of the communist authorities. The new superiors were expected to be full of loyalty and closely cooperate and support the social and political changes taking place.
Keywords: Orthodox Church; religious policy; Office for Religious Affairs; Doroszkiewicz, Włodzimierz Aleksiejewicz (Bazyli; zwierzchnik Polskiego Autokefalicznego Kościoła Prawosławnego; 1914-1998)